2020
DOI: 10.4103/jos.jos_66_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the perception of smile esthetics, in frontal view, with mandibular laterognatism, through the eye-tracking technique

Abstract: OBJECTIVES: To evaluate the perception of esthetics and the attractiveness of the smile, in frontal view, with mandibular asymmetry, through the eye-tracking. MATERIALS AND METHODS: OGAMA software and The Eye Tribe Tracker hardware were used to obtain eye tracking in certain areas of interest on the face. To simulate asymmetry, Photoshop® image editing software was used to create a vertical reference line to the midline of the face and make it symmetrical with control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…These differences between genders were interesting findings since most studies on visual perception in dentistry have not compared male and female faces and smiles. 5,7,10 Previous studies have reported that in men, the smile was responsible for 49% and 69% of the perception of the attractiveness of aligned teeth by men and women, respectively. 11 Our findings contradict these results since the change in smile esthetics did not have such an impact on the female face compared to the male face.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These differences between genders were interesting findings since most studies on visual perception in dentistry have not compared male and female faces and smiles. 5,7,10 Previous studies have reported that in men, the smile was responsible for 49% and 69% of the perception of the attractiveness of aligned teeth by men and women, respectively. 11 Our findings contradict these results since the change in smile esthetics did not have such an impact on the female face compared to the male face.…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, researchers in visual perception have become more interested in using laypeople as study participants 5 , 7 , 11 because laypeople represent the view of patients, whose opinions are very important to clinicians developing a treatment plan in any specialty within dentistry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perception of the smile attractiveness of an individual, though distinct, is nurtured by social and demographic factors. [ 3 ] Thought to be primarily subjective in nature, perception is shown to be dictated by an objective assessment of attractiveness, faintly masked by certain personal preferences. [ 4 ] Also, patients and laypeople (LP) were found to differ with specialists in judging smile attractiveness.…”
Section: Introductionmentioning
confidence: 99%